2015
DOI: 10.1108/ijm-06-2014-0137
|View full text |Cite
|
Sign up to set email alerts
|

A good or bad transition from school to work: who is responsible?

Abstract: Purpose – The purpose of this paper is to analyse the determinants of the quality of the first job in Flanders (Belgium). The authors differentiate between circumstances on the one hand – individual characteristics beyond the control of the individuals such as gender or the unemployment rate at labour market entry – and efforts on the other hand – characteristics that are at least partly under the individuals’ control such as their educational attainment or labour motivation. The authors specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…According to Scherer (2004) , the labor market entry and a successful transition from school to work are of crucial importance for subsequent career chances, it is a good start to look at the possibly different opportunities here for men and women. Defloor et al (2015) found that the quality of a person’s first job is largely dependent on personal effort, although circumstances, for example, gender do have a considerable influence on these efforts. This would, therefore, suggest that a difference of jobs between men and women is due to a difference in effort spent between men and women when searching for their first job.…”
Section: Background Theory and Hypothesesmentioning
confidence: 99%
“…According to Scherer (2004) , the labor market entry and a successful transition from school to work are of crucial importance for subsequent career chances, it is a good start to look at the possibly different opportunities here for men and women. Defloor et al (2015) found that the quality of a person’s first job is largely dependent on personal effort, although circumstances, for example, gender do have a considerable influence on these efforts. This would, therefore, suggest that a difference of jobs between men and women is due to a difference in effort spent between men and women when searching for their first job.…”
Section: Background Theory and Hypothesesmentioning
confidence: 99%
“…Therefore, schooling decisions may be closely related to changes in the labor market and their impact on the family and community. Indeed, Defloor et al (2015) conclude that the quality of the first job depends considerably on individual effort, but that this effort depends largely on such circumstances as educational attainment and the situation of the labor market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet, most studies on early careers rely on observations of individual employees, their characteristics, resources and behaviours (e.g. Defloor et al, 2015;De Lange et al, 2014;Akkermans et al, 2014), while few studies have paid attention to demand-side factors and the preferences and decision-making process of managers (Wolbers, 2014;De Wolf and van der Velden, 2001). This study therefore focusses on the retention decisions of managers to gain a better understanding of which factors influence the probability of job retention for young intermediate-level educated employees.…”
Section: Introductionmentioning
confidence: 99%